A far‐red fluorescent probe for flow cytometry and image‐based functional studies of xenobiotic sequestering macrophages. (24th June 2015) - Keswani, Rahul K.; Yoon, Gi S.; Sud, Sudha; Stringer, Kathleen A.; Rosania, Gus R.
Abstract Clofazimine (CFZ) is an optically active, red‐colored chemotherapeutic agent that is FDA approved for the treatment of leprosy and is on the World Health Organization's list of essential medications. Interestingly, CFZ massively accumulates in macrophages where it forms crystal‐like drug inclusions (CLDIs) after oral administration of the drug in animals and humans. The analysis of the fluorescence spectra of CLDIs formed by resident tissue macrophages revealed that CFZ, when accumulated as CLDIs, undergoes a red shift in fluorescence excitation (from Ex: 540–570 to 560–600 nm) and emission (Em: 560–580 to 640–700 nm) signal relative to the soluble and free‐base crystal forms of CFZ. Using epifluorescence microscopy, CLDI(+) cells could be identified, relative to CLDI(−) cells, based on a >3‐fold increment in mean fluorescence signal at excitation 640 nm and emission at 670 nm. Similarly, CLDI(+) cells could be identified by flow cytometry, based on a >100‐fold increment in mean fluorescence signal using excitation lasers at 640 nm and emission detectors >600 nm. CLDI's fluorescence excitation and emission was orthogonal to that of cell viability dyes such as propidium iodide and 4, 6‐diamidino‐2‐phenylindole dihydrochloride (DAPI), cellular staining dyes such as Hoechst 33342 (nucleus) and FM 1‐43 (plasma membrane), as well as many other fluorescently tagged antibodies used for immunophenotyping analyses. In vivo, >85% of CLDI(+) cells in the peritoneal exudate were F4/80(+) macrophages and >97% of CLDI(+) cells in the alveolar exudate were CD11c(+). Most importantly, the viability of cells was minimally affected by the presence of CLDIs. Accordingly, these results establish that CFZ fluorescence in CLDIs is suitable for quantitative flow cytometric phenotyping analysis and functional studies of xenobiotic sequestering macrophages. © 2015 International Society for Advancement of Cytometry